Tips for making business plan presentations (Part 1) - Mat Zin, Sakinah; Nik Jaafar, Nik Fazlin Hiryati; Nik Hassan, Nik Fakrulhazri; Ibrahim, Norlaila; Kamaludin, Mohd Ariff; Ismail, Irwan; Md Noor, Jannah Munirah; Jasni, Nurul Syuhada; Mohamed Ahmad, Ferozah Haini (Universiti Teknologi MARA, Terengganu, 2018)
Business plan presentation is indispensable because in up to date's business environment, the competition is getting more competitive. It is no longer enough for you to have the necessary capability to come with a good business proposal, you should also be able to talk well and present yourself attractively to the panels. Giving a good business presentation to let other people know what the business all about is for the purpose of getting business referral.